A Review of Countermovement and Squat Jump Testing Methods in the Context of Public Health Examination in Adolescence: Reliability and Feasibility of Current Testing Procedures - Petrigna, Luca; Karsten, Bettina; Marcolin, Giuseppe; Paoli, Antonio; D’Antona, Giuseppe; Palma, Antonio; Bianco, Antonino (Frontiers in Physiology, 2019)
Background In the context of a public health physical fitness (PF) examination in adolescence, a countermovement jump (CMJ) and a squat jump (SJ) are two vertical jump (VJ) tests widely used to evaluate lower limb muscle strength and power, respectively. The main criticism of both the CMJ and SJ test is the lack of test standardization. Therefore, the objectives of this review are: (a) to gather information about both jumps; (b) to investigate whether it is possible to identify common procedures referred to in the CMJ and SJ technical execution, and (c) to design standard operating procedures (SOPs) to promote CMJ and SJ standardization in an adolescent population aged 12–18 years. Methods The review partially adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement (PRISMA). Due to growing attention in monitoring physical health through field tests in recent years, articles were collected using the PubMed, Web of Science, and Scopus databases from January 2009 to July 2019. Original articles in which CMJ or SJ were used to assess the muscular strength in adolescents were eligible for further analysis. Articles written in English was imposed as a limit. Results A total of 117 studies met the inclusion criteria. The description of the CMJ and SJ test procedures was different within the literature, with discrepancies in the jump technique, number of jumps, and measurement devices used. Conclusions A lack of method standardization for both the CMJ and the SJ test was identified. Based on the literature, SOPs for both VJs were proposed. These are useful in the context of public health PF examination in adolescents, as they facilitate an unbiased comparison of jump performance data between published studies.